Disentangling the Effects of Climate, Vegetation, Soil and Related Substrate Properties on the Biodegradability of Permafrost‐Derived Dissolved Organic Carbon. Issue 11 (11th November 2019) - Liu, Futing; Kou, Dan; Abbott, Benjamin W.; Mao, Chao; Chen, Yongliang; Chen, Leiyi; Yang, Yuanhe
Key Points: Dissolved organic carbon (DOC) from thawed permafrost had high biodegradability, with an average of 21.7% loss over a 28‐day incubation The biodegradability of permafrost‐derived DOC was larger than or equal to that in active‐layer across 72% of sampling sites Spatial and vertical variations in DOC biodegradability were jointly determined by vegetation types, soil properties, and DOC composition Abstract: Dissolved organic carbon (DOC) plays an important role in permafrost carbon cycle. However, substantial uncertainties remain about what determines the biodegradability of permafrost‐derived DOC and how the biodegradability varies between permafrost and active‐layer soils at a regional scale. Here, we conducted an incubation experiment with DOC leached from permafrost and active‐layer soils along a 1, 000‐km permafrost transect on the Tibetan Plateau. Our results showed that permafrost‐derived DOC had high biodegradability, with an average of 21.7% loss of DOC over a 28‐day incubation. The biodegradability of DOC leached from permafrost soils was larger than or equal to that in active‐layer within 72% of sampling sites. Our results also revealed that variation in DOC biodegradability in permafrost soils and its difference with that in active‐layer soils were jointly determined by vegetation types, soil properties, and related DOC composition. The biodegradability of permafrost‐derived DOC in alpine steppe and meadow was lower than that in swamp meadow. It also declined with the decreasing soil carbon: nitrogen ratio, increasing pH, clay content, DOC molecular weight, and its degradation degree. Similarly, the variability in the difference of DOC biodegradability between permafrost and active‐layer soils also resulted from the differences of three types of above‐mentioned factors between the two layers. These results suggest that permafrost thawing‐induced DOC release could intensify permafrost carbon‐climate feedback due to its vulnerability to microbial decomposition, with its impact depending on vegetation, soil, and substrate properties. Plain Language Summary: When permafrost thaws, a portion of the organic matter within permafrost can be dissolved into water and transported as dissolved organic carbon (DOC). If permafrost DOC is easily broken down by microbes, it could accelerate carbon loss from permafrost, reinforcing climate warming. Permafrost DOC is traditionally regarded as more biodegradable than DOC from active‐layer (seasonally frozen) soils, but it is unknown how general this pattern is since these differences are usually observed within a small geographic area. In this study, we measured DOC biodegradability in 25 sites across the Tibetan alpine permafrost region and observed that permafrost‐derived DOC biodegradability was not always higher than active‐layer soils, but 72% of sampling sites had higher DOC biodegradability in permafrost layer than or equal to that in the active layer. We also found that vegetation types, soil properties, and related DOC composition explained the variation of permafrost‐released DOC biodegradability and its difference between permafrost and active‐layer soils. This work highlights that permafrost‐derived DOC is vulnerable to microbial decomposition upon thaw, potentially intensifying the permafrost carbon‐climate feedback.